Living Qur'an of Pesantren Women: A Manifestation of QS. An-Nisa 34 in A Woman Leadership Role of Nyai Munjidah Wahab - Umniyatul Labibah; Imam Taufiq; Moh. Yasir Alimi (UIN Sunan Kalijaga Yogyakarta, 2022)
This article discusses the study of the living Qur'an of “women’s Pesantren” with a character study approach namely Nyai Munjidah Wahab. So far, women’s Pesantren have been stigmatized as a group of women who only act as “konco wingking”, and their scope of work is only in the domestic or internal area of the pesantren. The leadership of “women’s pesantren” is often considered as a